The adult with tetralogy of Fallot: what the clinical cardiologist needs to know - Chávez-Saldívar, Samantha (2021)
Tetralogy of Fallot (TOF) is the most common cyanotic congenital heart disease. After more than seven decades of the first palliative surgery, TOF prognosis has changed dramatically. With a higher survival into adulthood, the clinical cardiologist faces challenges in the management of this population, from severe pulmonary regurgitation to heart failure and ventricular arrhythmias. In this review, we will describe the most relevant aspects of the care of adults with this disease.